The impact of cohabitation without marriage on intergenerational contacts: A test of the diffusion theory - Tiziana Nazio; Chiara Saraceno (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2010)
In the literature, cohabitation rather than marriage is presented as an indicator of weakening intergenerational ties, either as a cause or an effect. In this paper we compare the frequency of face to face and phone contacts between parents and their married and unmarried children living with a partner in two countries - Italy and the UK - where the incidence of cohabiting instead of, or before, marrying is very different. Our analysis of empirical evidence, based on an ordered category response multilevel model, does not support the hypothesis that in Italy, where cohabitation is still an exception, differences in parent-adult children contacts between cohabitant and married children are much greater than in the UK, where cohabitation is more common and since a longer time. While in the UK cohabitation does not seem to have an impact on frequency of contacts, in Italy, cohabitation only increases the (marginal) proportion of those who do not visit and lowers slightly that of those who visit on a daily basis against weekly or monthly, but not the frequency of phone contacts. Also the hypothesis that duration of cohabitation makes a difference is not supported. The main difference we found is that cohabitant couples in Italy have a slight tendency to live farther away from their parents than married ones. This affects frequency of face to face contacts. These findings support the thesis that in both countries cohabitation and marriage are becoming increasingly similarly accepted patterns of partnership formation, which do not affect in distinct ways intergenerational relationships, although the differential residential choices of married and cohabitant couples in Italy remains an issue to be explained. Findings also support the thesis that, in Italy, cohabiting instead of marrying is still to some extent a polarized phenomenon: in the majority of cases it is supported, if not rendered possible, by parents, while in a small minority it is accompanied by estrangement.
Keywords: 300; cohabitation; intergenerational contacts; individualization; Lebensgemeinschaft; Generationenbeziehungen; Solidarität; Großbritannien; Italien